1992
DOI: 10.1002/ijc.2910510517
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitions by 6‐hydroxydopamine and neostigmine singly or together of gastric carcinogenesis induced by N‐methyl‐N′‐nitro‐n‐nitrosoguanidine in wistar rats

Abstract: The effects of chemical sympathectomy induced by 6-hydroxydopamine (6-OHDA) and administration of the acetylcholinesterase inhibitor neostigmine, singly or together, on gastric carcinogenesis induced by N-methyl-N'-nitro-N-nitrosoguanidine (MNNG), and on the tissue catecholamine concentration of the gastric wall and the labeling index of the gastric mucosa, were investigated in inbred Wistar rats. Rats received s.c. injections of neostigmine (0.075 mg/kg), and/or i.p. injections of 6-OHDA (42 mg/kg twice withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Several studies highlight the role of the sympathetic and parasympathetic nervous systems in the development of tumors and metastases. For example, our results are in accordance with the study of Tatsuta et al [13] who showed that prolonged intraperitoneal treatment with 6-OHDA attenuated the incidence of N-methyl-N´-nitro-N-nitrosoquanidine (MNNG) induced gastric cancer in rats. Likewise, Raju et al [5] demonstrated that bilaterally sympathectomized rats develop significantly smaller, more diffuse in appearance, and less invasive tumors compared with sham operated rats.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies highlight the role of the sympathetic and parasympathetic nervous systems in the development of tumors and metastases. For example, our results are in accordance with the study of Tatsuta et al [13] who showed that prolonged intraperitoneal treatment with 6-OHDA attenuated the incidence of N-methyl-N´-nitro-N-nitrosoquanidine (MNNG) induced gastric cancer in rats. Likewise, Raju et al [5] demonstrated that bilaterally sympathectomized rats develop significantly smaller, more diffuse in appearance, and less invasive tumors compared with sham operated rats.…”
Section: Discussionsupporting
confidence: 93%
“…sympathectomy, administration of β-blockers) have shown stimulatory eff ect of sympathetic nervous system on several experimental tumors, as well. For example, chemical sympathectomy performed by 6-OHDA attenuated the incidence of N-methyl-N´-nitro-N-nitrosoquanidine (MNNG) induced gastric cancer in rats (Tatsuta et al 1992), inhibited the growth pattern of LPC-1 plasmacytoma tumors in mice (Grzanna et al 1985), and also decreased the incidence of intra-abdominal fi brosarcoma tumors in rats and prolonged their survival (Lackovicova et al 2011). Similarly, bilateral surgical sympathectomy in rats resulted in the development of significantly smaller and less invasive tongue tumors than in sham-operated animals (Raju et al 2007;Raju et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…16 How ever, it should be considered that pharmacological modulation or surgical transection of the autonomic nerves during cancer, including pancreatic cancer, with agents that block β-adrenergic or cholinergic signalling is a quite an old concept, dating back to the end of 1980s. [91][92][93][94][95][96] Indeed, several studies showed the beneficial effects of administering propanolol as an unselective β-blocker with reduced pancreatic cancer incidence in hamsters with ethanol-induced pancreatitis. 97 At the cellular level, β-adrenergic receptors were shown to stimulate the proliferation and migration of human pancreatic cancer cells by cAMP-dependent signalling.…”
Section: Nerves As Modulators Of Disease Progressionmentioning
confidence: 99%